2020
DOI: 10.1016/j.tmp.2020.100714
|View full text |Cite
|
Sign up to set email alerts
|

The link among board characteristics, corporate social responsibility performance, and financial performance: Evidence from the hospitality and tourism industry

Abstract: The aim of this study is twofold: to explore whether board characteristics (i.e. a sustainability committee, board independence, board diversity, and board diligence) lead to greater corporate social responsibility (CSR) performance, and to test whether CSR performance enhances firms' financial performance in the hospitality and tourism (H&T) industry. Data were collected from the Thomson Reuters Eikon database for the H&T firms listed there between 2011 and 2018. We employed panel data analysis, after which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
112
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(155 citation statements)
references
References 111 publications
12
112
3
Order By: Relevance
“…The articles included in this review study the relationship between the diversity of the board of directors and the CSR using multiple dependent variables, as can be seen in Figure 2. The following stand out among them: CSR as social responsibility, social performance or sustainability performance (Bear et al, 2010; Beji et al, 2020; Boulouta, 2013; Byron & Post, 2016; Cruz et al, 2019; Fernandez et al, 2019; Francoeur et al, 2019; García‐Sánchez et al, 2018; Hafsi & Turgut, 2013; M. A. Harjoto & Rossi, 2019; Landry et al, 2016; Macaulay et al, 2018; McGuinness et al, 2017; Setó‐Pamies, 2015; Uyar et al, 2020; Zhang et al, 2013; Zhuang et al, 2018), environmental performance (Birindelli et al, 2019; Cordeiro et al, 2020; Elmagrhi et al, 2018; Lu & Herremans, 2019; Walls et al, 2012), environmental investment (Atif et al, 2020; Jiang & Akbar, 2018; Wei et al, 2017), environmental lawsuits (Liu, 2018), corporate philanthropy or charitable contributions (Campopiano et al, 2019; Jia & Zhang, 2013; Williams, 2003; Wonsuk & Abebe, 2016; Zhang et al, 2018) and CSR assurance (Liao et al, 2018). Rodriguez‐Dominguez et al (2009) analyze the process of creating and implementing a code of ethics.…”
Section: Discourse and Trends In Board Gender Diversty And Corporate mentioning
confidence: 99%
See 1 more Smart Citation
“…The articles included in this review study the relationship between the diversity of the board of directors and the CSR using multiple dependent variables, as can be seen in Figure 2. The following stand out among them: CSR as social responsibility, social performance or sustainability performance (Bear et al, 2010; Beji et al, 2020; Boulouta, 2013; Byron & Post, 2016; Cruz et al, 2019; Fernandez et al, 2019; Francoeur et al, 2019; García‐Sánchez et al, 2018; Hafsi & Turgut, 2013; M. A. Harjoto & Rossi, 2019; Landry et al, 2016; Macaulay et al, 2018; McGuinness et al, 2017; Setó‐Pamies, 2015; Uyar et al, 2020; Zhang et al, 2013; Zhuang et al, 2018), environmental performance (Birindelli et al, 2019; Cordeiro et al, 2020; Elmagrhi et al, 2018; Lu & Herremans, 2019; Walls et al, 2012), environmental investment (Atif et al, 2020; Jiang & Akbar, 2018; Wei et al, 2017), environmental lawsuits (Liu, 2018), corporate philanthropy or charitable contributions (Campopiano et al, 2019; Jia & Zhang, 2013; Williams, 2003; Wonsuk & Abebe, 2016; Zhang et al, 2018) and CSR assurance (Liao et al, 2018). Rodriguez‐Dominguez et al (2009) analyze the process of creating and implementing a code of ethics.…”
Section: Discourse and Trends In Board Gender Diversty And Corporate mentioning
confidence: 99%
“…Francoeur et al, 2019;García-Sánchez et al, 2018;Hafsi & Turgut, 2013;M. A. Harjoto & Rossi, 2019;Landry et al, 2016;Macaulay et al, 2018;McGuinness et al, 2017;Setó-Pamies, 2015;Uyar et al, 2020;Zhang et al, 2013;Zhuang et al, 2018), environmental performance(Birindelli et al, 2019;Cordeiro et al, 2020;Elmagrhi et al, 2018;Lu & Herremans, 2019;Walls et al, 2012), environmental investment(Atif et al, 2020;Jiang & Akbar, 2018;Wei et al, 2017), environmental lawsuits(Liu, 2018), corporate philanthropy or charitable contributions(Campopiano et al, 2019;Jia & Zhang, 2013;Williams, 2003;Wonsuk & Abebe, 2016;Zhang et al, 2018) and CSR assurance(Liao et al, 2018) Rodriguez-Dominguez et al (2009). analyze the process of creating and implementing a code of ethics.…”
mentioning
confidence: 99%
“…The sustainability indicators (particularly, a policy sustainable packaging, but also a sustainability committee, energy use, renewable energies) also have positive effects on the financial performance of considered companies. Moreover, CSR policies, enforced at the level of board management, may induce "a domino effect" further down, at the level of executive management and upon the actions of all employees, as Uyar et al [15] (p. 9) also proved. We have highlighted that the renewable energy and corporate governance board committee had the utmost favorable effects on companies' value and earnings.…”
Section: Discussionmentioning
confidence: 94%
“…Since our findings revealed that board gender diversity has improved the overall companies' value and earnings, policymakers may set a minimum share of female representatives on board management of the European companies, to be enclosed within the CG rules. Women may heighten the existing activities of the companies by mostly orientation towards social and environmental actions [83], female representatives being "more philanthropically driven and community-oriented" than male counterparts [15] (p. 9), or more focused on reporting quality [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation